Bouzard Jr., W.C., We Have Heard with Our Ears, O God: Sources of the Communal Laments in the Psalms (Society of Biblical Literature Disssertation Series 159), Atlanta, GA, Scholars Press, 1997, 240 pp., ISBN 0788503545 - Rostom Maderna, Santiago (2004)
Fil: Rostom Maderna, Santiago. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras; Argentina